First report of kinorhynchs from Hokkaido, Japan, including a new species of Pycnophyes (Pycnophyidae: Homalorhagida) - Yamasaki, Hiroshi; Kajihara, Hiroshi; Mawatari, Shunsuke F. (Zootaxa, 2012)
We describe and illustrate Pycnophyes oshoroensis sp. nov. from Hokkaido, northern Japan. This species is characterized by (1)a trunk 646–775μm long, and a presence of (2) middorsal elevation on segments 2–9, (3) anterior middorsal projection onsegment 2, (4) even anterior tergal margin of segment 1, (5) reticulate cuticular area on anterior margin of tergal, episternal, andmidsternal plates of segment 1, (6) laterodorsal setae on segments 2–9, (7) paralateral setae on segments 1, 2, 4, 6, 7, 8 and 10,(8) ventrolateral setae on segments 1, 5 and 10, (9) ventromedial setae on segments 3–9, and (10) subcuticle thickening areas inparaventral position on segments 9 and 10. In addition, we provide morphological descriptions for two species found fromHokkaido, Japan in this study: Cephalorhyncha asiatica (Adrianov, 1989) and Kinorhynchus yushini Adrianov, 1989. This is the first report of kinorhynchs from Hokkaido and the first report of C. asiatica from Japanese waters.